2018
DOI: 10.21873/anticanres.12511
|View full text |Cite
|
Sign up to set email alerts
|

Potent Antitumour Effects of Novel Pentabromobenzylisothioureas Studied on Human Glial-derived Tumour Cell Lines

Abstract: Our findings indicated that modified ZKKs show promise for the treatment of glioma-derived brain tumours.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 45 publications
(48 reference statements)
0
8
0
Order By: Relevance
“…However, their reports do not provide detailed information regarding the duration of incubation with ZKK-3, or whether the results are associated with the total kinase level or only to the level of its non-phosphorylated form. Other research performed in the T98G cell line indicates that a 48-h incubation with 10 µM ZKK-3 does not alter PKD1 expression, but significantly decreases the expression level of pPKD1 (Ser 916) (26). The present results indicated that ZKK-3 did not significantly change the expression of total PKD1 in GBM cells in vitro .…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations
“…However, their reports do not provide detailed information regarding the duration of incubation with ZKK-3, or whether the results are associated with the total kinase level or only to the level of its non-phosphorylated form. Other research performed in the T98G cell line indicates that a 48-h incubation with 10 µM ZKK-3 does not alter PKD1 expression, but significantly decreases the expression level of pPKD1 (Ser 916) (26). The present results indicated that ZKK-3 did not significantly change the expression of total PKD1 in GBM cells in vitro .…”
Section: Discussionmentioning
confidence: 91%
“…Therefore, intensive research is focused on developing novel treatment strategies. S-benzylisothiourea derivatives have been investigated, with in vitro results validating their proapoptotic and cytotoxic properties against various neoplastic cells, including several types of leukemia (20,21), prostate adenocarcinoma (22) and glioma (19,26). Furthermore, compounds from this group have demonstrated greater cytotoxicity against human glioblastoma cells in vitro compared with the clinically used compound temozolomide (26).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Modification of a biologically active molecule by introducing various substituents may result in an unexpected effect. For example, the addition of chlorine in the structure of a compound may result in its low or no cytotoxic activity, as in the case of BEN compound, which showed very little or no cytotoxicity towards low-(G1) and high-grade (G4) glioma cells [97]. TBB, TBI, and DMAT compounds show strong CK2 inhibitory properties, while S-pentabromobenzylisothiourea derivatives, which are structurally similar to polybrominated compounds (TBB, TBI, DMAT), show a distinct protein kinase inhibition profile.…”
Section: Cx-4945mentioning
confidence: 99%